Biotic and abiotic factors affecting soil microbial carbon use efficiency - Tang, Xinyu; Li, Zhenxin; Yuan, Jihong; Yu, Weirui; Luo, Wenbo (Frontiers in Plant Science, 2024)
Soil microbial carbon use efficiency (CUE) refers to the efficiency of microorganisms in converting absorbed carbon into their own biomass carbon. Soil microbial CUE is a key parameter to understanding the soil carbon cycle. Biotic and abiotic factors are widely considered to be important factors influencing CUE. However, the related underlying mechanisms remain unclear. This review elaborates on the concept of soil microbial CUE and the various approaches used for its measurement.We reviewed the effects of various abiotic factors, such as temperature, soil moisture, pH, nutrient addition, and substrate type, and biotic factors, such as microbial community structure and diversity, on CUE. Finally, we discussed the focus areas that future studies need to further explore. We hope this review can provide a comprehensive understanding of the factors impacting soil microbial CUE, which is a fundamental step to improving soil carbon storage capacity.